Nelson's Ridge Subdivision: conservation approach to rural subdivision development - DeNarvaez, Felipe Spencer (Kansas State University, 2011)
A 2009 research report by the U.S. Census Bureau and the National Resources Inventory predicts that the developed area in the United States will increase by 54.4 million acres during the next 25 years (McMahon 2010, 2). America’s rural landscape and character is replaced everyday by “placeless” neighborhoods with limited emphasis on conservation efforts. The intent of this report is to demonstrate the benefits of applying conservation design principles to the development of a conservation subdivision in rural Kansas. A 132 acre tract of land, currently known as Nelson’s Ridge, is planned and designed for a subdivision development. The property is located just east of Manhattan, Kansas. The site includes a tributary drainage corridor surrounded by woodlands, existing agriculture fields and upland prairie. It is located no more than a mile from existing amenities of a growing residential and commercial corridor along Highway 24 in Pottawatomie County. The preliminary plat designed by local engineering firm Schwab-Eaton, demonstrates America’s typical or “conventional” approach to subdivision design (Arendt, 1996). The alternative approach is known as a low-impact development or “conservation development” (Gause 2007). After completing a thorough site inventory and analysis, two preliminary designs eventually led to a final conceptual master plan. The two preliminary designs included contemporary and neo-traditional schemes, each portraying conservation principles in alternative ways. Fully understanding the two design alternatives allowed for a balanced and more cohesive final design that incorporated the most positive aspects of both conservation approaches. The preliminary plat and the conservation design were then compared and analyzed in terms of demonstrated design principles and their economic feasibility. This project provides an example for rural subdivision development in Pottawatomie County, Kansas. The project provides decision makers with a conceptual master plan for Nelson’s Ridge that implements conservation subdivision design principles. This project will educate developers, homeowners and the public about design alternatives for subdivision development. The comprehensive analysis of the proposed design will provide important insight into the benefits and limitations of implementing conservation principles into a development.
Keywords: Conservation; Subdivision development; Community based agriculture; Green infrastructure; Cluster development; Water conservation; Landscape Architecture (0390)